Substitution and Ellipsis in the English to Arabic Translation of Political Opinion Texts - Lulu, Reem Adib; Habeeb, Luwaytha S. (International Journal of Psychosocial Rehabilitation, 2020)
Cohesive markers include substitution and ellipsis link sentences together and unite the whole text. These markers can be used differently in different languages due to their different grammatical structures. Therefore, while translating from the source language (SL) to the target language (TL), translators may not translate all of the cohesive markers or may incorrectly translate them which affects the message of the SL. This study uses Halliday and Hasan’s (1976) model of cohesion to identify substitution and ellipsis used in Arabic and English political texts. The study also adopts Nida’s translation techniques (1964) to identify the translation techniques which are used to translate English substitution and ellipsis devices into Arabic. The source English texts are taken from the online editions of The Washington Post and New York Times, while their translated Arabic versions are taken from the online Arabic newspaper, Asharq Al-Awsat. The findings reveal that substitution cohesive device is used in few examples in both Arabic and English texts. Ellipsis devices are used in more frequencies in English texts than in Arabic ones. The study also reveals that only one technique of Nida is found in translating the English substitution cohesive devices, which is, alteration, whereas two of the translation techniques of Nida, alternation and addition, are found in translating the English Ellipsis cohesive devices. One new technique is also found in this study, namely ‘sustaining’, as named by Lulu (2015).